PENGARUH CORPORATE SOCIAL RESPONSIBILITY, KINERJA KEUANGAN, DAN INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018 - 2022 - Novpitasari; Erika Astriani Aprilia (Journal of Management and Business, 2024)
This study aims to analyze the influence of corporate social responsibility, financial performance, and intellectual capital to firm value. This research uses quantitative methods. The number of samples used were 23 banking sector companies. The sampling technique used is purposive sampling. Secondary data was obtained using the annual financial report search method and the annual report of banking sector companies for 2018-2022 and processed using eviews 12. The analysis technique used is descriptive statistical test, classic assumption test, panel data regression analysis and hypothesis testing. The results showed that the F test obtained simultaneously the independent variables of corporate social responsibility, financial performance, and intellectual capital have an effect on the dependent variable of firm value. The results of the analysis test using the t test on corporate social responsibility variables have no effect on firm value, while the t test on financial performance and intellectual capital variables have an effect on firm value.